2019
DOI: 10.1017/s0022109019000590
|View full text |Cite
|
Sign up to set email alerts
|

Busy Directors and Shareholder Satisfaction

Abstract: Prior research has examined the firm-level performance implications of “busy” boards. Firm-level analysis, however, masks important heterogeneity in the time constraints and expertise of individual busy directors. We develop and validate shareholder voting as a proxy for shareholders’ satisfaction. Our director-specific tests provide compelling evidence that the potential costs of busy directors outweigh their benefits. At the same time, we uncover new sources of heterogeneity among busy directors. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
5
17
1
Order By: Relevance
“…In other words, 33% of the boards in the sample are busy. The value is relatively higher than those (20–27%) reported in prior literature (e.g., Perry and Peyer, 2005; Chen and Guay, 2018; Moursli, 2019).…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…In other words, 33% of the boards in the sample are busy. The value is relatively higher than those (20–27%) reported in prior literature (e.g., Perry and Peyer, 2005; Chen and Guay, 2018; Moursli, 2019).…”
Section: Resultscontrasting
confidence: 68%
“…Research method 3.1 Board busyness As previously mentioned, board busyness is frequently defined as outside directors who serve on three or more boards. Thus, following prior studies (e.g., Chen and Guay, 2018), the measure of board busyness (BB) is the proportion of the directors on a board who are busy, i.e., sit on three or more boards. Specifically, BB is the number of outside directors who hold three or more board appointments scaled by the number of directors on the board.…”
Section: Board Busyness and Firm Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Feldman (2016) found dual directors displaying a tendency to expropriate the wealth of minority shareholders in spinoff firms. In addition, busy boards have been documented to be less effective in terms of monitoring function (Chen and Guay 2020;Core et al 1999). Using the sample of Forbes 500 firms, Fich and Shivdasani (2005) found that firms with busy outside directors are associated with lower profitability and firm value.…”
Section: Hypothesis Developmentmentioning
confidence: 99%